Analisis Penerapan Sistem Informasi Akuntansi pada JM Hotel Kuta Lombok - Sri Rahmawati, Baiq Maura; Hairi, Refreandi; Yohana, Yohana (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study aims to analyze the implementation of the accounting information system (AIS) at JM Hotel Kuta Lombok, focusing on its effectiveness, efficiency, and operational challenges. The research employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The findings reveal that AIS implementation at JM Hotel is relatively adequate in supporting financial transaction recording, internal control, and managerial decision-making. However, challenges include limited human resources with insufficient technological literacy and system infrastructure that requires improvement. These results imply that hotel management needs to enhance AIS application quality to better support operational performance and financial control.